Bimbingan Teknis Penggunaan Platform Yahoo Finance Untuk Pemilihan Saham Bagi Investor Pemula (Newbie) - Hesti Murwaniputri; Aprianto La’lang Kuddy (Jurusan Manajemen dan Bisnis Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2022)
Community service activities in the form of technical guidance aimed at increasing knowledge and skills based on science and technology, increasing motivation and interest in investing for novice investors in Jayapura City. This technical guidance to expected to make it easier for novice investors to make stock selections. The method used in this service is in the form of lectures and demonstrations accompanied by questions andanswers via zoom media with participants due to PPKM. The obstacle faced by novice investors is that it is difficult to choose good and cheap stocks so that they only